Evaluation of sensitivity and specificity of tests for breast cancer (Texas Journal of Medical Science, 2025)
Breast cancer (BC) is one of the most common malignant neoplasms in women worldwide and a leading cause of cancer-related mortality. Early diagnosis remains a pressing issue, as treatment effectiveness and survival prognosis directly depend on the stage at which the tumor is detected. The aim of this study was to evaluate the diagnostic accuracy of laboratory and instrumental methods used to detect breast cancer and to determine their optimal combination to improve diagnostic efficiency . The study included data from 150 women undergoing examination for suspected breast cancer. A comparative analysis of the sensitivity and specificity of mammography, ultrasound, magnetic resonance imaging (MRI), and the serological markers CA 15-3 and CEA was conducted. Morphological confirmation of the diagnosis (biopsy) was taken as the "gold standard." The results showed that MRI achieved the highest sensitivity (95%), while mammography and ultrasound remained the mainstays of primary screening (86% and 80%, respectively). The combined use of instrumental methods and laboratory markers achieved a sensitivity of 97% and a specificity of 92%, significantly increasing diagnostic accuracy . Thus , the study confirms that the integration of various diagnostic approaches ensures maximum reliability in the early detection of breast cancer and can serve as the basis for optimizing screening algorithms and clinical diagnostics.